2016
DOI: 10.18632/oncotarget.8651
|View full text |Cite
|
Sign up to set email alerts
|

Sulfasalazine impacts on ferroptotic cell death and alleviates the tumor microenvironment and glioma-induced brain edema

Abstract: The glutamate transporter xCT (SCL7a11, system Xc-, SXC) is an emerging key player in glutamate/cysteine/glutathione homeostasis in the brain and in cancer. xCT expression correlates with the grade of malignancy. Here, we report on the use of the U.S. Food and Drug Administration and EMA-approved xCT inhibitor, sulfasalazine (SAS) in gliomas. SAS does not affect cell viability in gliomas at concentrations below 200 μM. At higher concentrations SAS becomes gliomatoxic. Mechanistically SAS inhibits xCT and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
80
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 34 publications
5
80
0
1
Order By: Relevance
“…Cell cycle analysis was performed according to Sehm et al [32]. Briefly, cells were seeded on culture dishes and kept under standard conditions for 3 days.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle analysis was performed according to Sehm et al [32]. Briefly, cells were seeded on culture dishes and kept under standard conditions for 3 days.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, cells were isolated, washed thrice in PBS and resuspended in hypolysis buffer containing 0.1% sodium citrate, 0.1% Triton X-100, and 100 g/ml RNAse A. Nuclei were then stained with 7AAD and analyzed by fluorescence-activated cell sorting (FACS) [32]. Cell cycle phases were analyzed with Cellsoft software.…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that SAS can induce ferroptosis in a series of cancer cell lines (HT‐1080, Calu‐1, 143B, BJeLR, BJeHLT) . SAS has also been used as a combined therapy to potentiate the therapeutic efficacy of other chemotherapeutics against glioma (Figure D) …”
Section: Ferroptosis Inducers For Cancer Therapymentioning
confidence: 99%
“…It was also found that sulfasalazine inhibits the glutamate transporter xCT (SCL7a11, system Xc - , SXC) and induces ferroptotic cell death in glioma cells. [2628] …”
Section: Small Molecules For Ferroptosis-based Cancer Therapymentioning
confidence: 99%